Diagnostic Performance of Gastric Imprint Smear for Determination of Helicobacter pylori Infection - J Al-Ali; F Al-Asfar; R Dhar; PM Dhar; K Kapila (Canadian Journal of Gastroenterology)
BACKGROUND: Despite the availability of several methods (invasive and noninvasive) for the diagnosis of Helicobacter pylori infection, no test is considered to be the ‘gold standard’. Endoscopy-based tests are regarded as the reference method in most studies.